Gamifying Grammar: Making Rules Fun in the Digital Age - Mothe, Dr. Prashant S. (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2025)
This research paper focuses on creating new and innovative ways to gamify grammar instruction to promote student engagement and learning outcomes in the age of digital imperialism. However, traditional methods of teaching grammar often result in a lack of student engagement and stress. Gamification is the integration of competition, rewards, or immersive storytelling into grammar lessons, where the technique can be used to enhance grammar lessons as a way to motivate and retain students. The purpose of this paper is to review the existing literature on gamification in education, review different gamified tools and platforms, and provide case studies that show successful implementation in different educational contexts. Further, it discusses the issues and limitations of gamifying grammar and the related issues and technological barriers to gamification. Overall, this study recommends integrating gamified approaches to grammar instruction and theorising that gamification can change the grammar instruction process into a more engaging and entertaining business for students.